2013
DOI: 10.1051/epjconf/20134012001
|View full text |Cite
|
Sign up to set email alerts
|

The disordered local moment approach to the spin-disorder resistivity of metallic ferromagnets

Abstract: Abstract. The spin-disorder resistivity (SDR) of transition metal ferromagnets (Fe, Co, Ni), rare-earth ferromagnet Gd, and Ni 2 MnSn Heusler alloy is determined from first principles. We identify the SDR at the Curie temperature with the residual resistivity of the corresponding system evaluated in the framework of the disordered local moment (DLM) model which has the zero spin-spin correlation function. The underlying electronic structure is determined in the framework of the tight-binding linear muffin-tin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…Theoretical studies have shown that the resistivity (ρ) in normal metals and alloys contains two dominant mechanisms, namely, the scattering of conduction electrons on impurities and other structural defects. [ 43–45 ] In our work, the gradual increase in the Pt 1‐x Gd x alloy compositions can be viewed as strong interface modification. With a much larger atomic radius of Gd (0.97 Å) than that of the Pt (0.63 Å), the replacement of Gd to Pt will result in an increase in lattice constant, which will modify the interface morphology.…”
Section: Resultsmentioning
confidence: 87%
“…Theoretical studies have shown that the resistivity (ρ) in normal metals and alloys contains two dominant mechanisms, namely, the scattering of conduction electrons on impurities and other structural defects. [ 43–45 ] In our work, the gradual increase in the Pt 1‐x Gd x alloy compositions can be viewed as strong interface modification. With a much larger atomic radius of Gd (0.97 Å) than that of the Pt (0.63 Å), the replacement of Gd to Pt will result in an increase in lattice constant, which will modify the interface morphology.…”
Section: Resultsmentioning
confidence: 87%
“…Indeed, electron-magnon (spindisorder) scattering usually reaches its maximum near the Curie temperature; above T C the spin-disorder mechanism is independent of T . Therefore, for some ferromagnetic metals and alloys (including FM HA), a distinct change in the slope of the ρ(T ) dependence can be expected at T C [20,21,22,23].…”
Section: Transport Propertiesmentioning
confidence: 99%
“…Зазвичай електрон-магнонний внесок в результуючий електроопір феромагнітного металу досягає свого максимуму біля температури Кюрі Т С , а вище Т С він вже не залежить від температури. Отже, для феромагнітних металів та стопів біля Т С на температурній залежності (Т) має спостерігатися, принаймні, зміна величини ТКЕ [24,25]. Існує декілька можливих механізмів появи неґативного ТКЕ в металах та стопах.…”
Section: рис 6 температурні залежності магнітної сприйнятливости лиunclassified